2011
DOI: 10.1631/jzus.b1101008
|View full text |Cite
|
Sign up to set email alerts
|

Association between SNP rs1800875, serum chymase and immunoglobulin E levels in patients with coronary heart disease

Abstract: Polymorphism rs1800875 of CMA1 may be associated with serum IgE level in CHD subjects, but not with chymase level in both groups. In GG homozygotes, high IgE level is a protective factor against coronary disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…59) TNNC1 implicates for heart failure and cardiomyopathies. 60) CMA1 is an ideal candidate for investigating the genetic predisposition to coronary heart disease. 61) BMP7 drives human adipogenic stem cells into metabolically active beige adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…59) TNNC1 implicates for heart failure and cardiomyopathies. 60) CMA1 is an ideal candidate for investigating the genetic predisposition to coronary heart disease. 61) BMP7 drives human adipogenic stem cells into metabolically active beige adipocytes.…”
Section: Discussionmentioning
confidence: 99%
“…Chymase, tryptase, and cathepsin G can degrade vascular endothelial cadherin, a molecule involved in the survival signaling of endothelial cells 93 . Even though one study reported that there was no correlation between serum chymase level and CAD 94 , it is local release of chymase and other mediators that would be important. Tryptase further leads to inflammation through protease activated receptors (PARs), that are also present on MC and can be stimulated by thrombin.…”
Section: Introductionmentioning
confidence: 96%